2016
DOI: 10.2135/cropsci2015.05.0295
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Reserves to Kernel Weight and Grain Yield Determination in Maize: Phenotypic and Genotypic Variation

Abstract: Maize (Zea mays L.) kernel weight (KW) and grain yield depend on plant growth during active grain filling and reserves use. The objective of our study was to analyze the phenotypic and genotypic variation in these traits in a family of recombinant inbred lines (RIL). In two field experiments we measured plant grain yield (PGY) and its components (KW and kernel number per plant, KNP), biomass production per plant and per kernel during active grain filling, and apparent reserves use (ARU) per plant (ARUP, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…The differences observed among hybrids on grain and corn ear yield was due to the timing of male and female flowering and individual weight of the corncob and grain. These results are consistent with those reported elsewhere (12,47) , who observed that grain weight depended on the growth and development of the plant and that the grain yield depended on the grain weight and the number of grains per row. Thus, it would be possible that the differences observed in grain yield between sowing seasons and among hybrids were because the plants sown in spring developed greater photosynthetic capacity due to a longer vegetative stage; which consequently results in an increased leaf area index as hypothesized by Reta et al (24) .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The differences observed among hybrids on grain and corn ear yield was due to the timing of male and female flowering and individual weight of the corncob and grain. These results are consistent with those reported elsewhere (12,47) , who observed that grain weight depended on the growth and development of the plant and that the grain yield depended on the grain weight and the number of grains per row. Thus, it would be possible that the differences observed in grain yield between sowing seasons and among hybrids were because the plants sown in spring developed greater photosynthetic capacity due to a longer vegetative stage; which consequently results in an increased leaf area index as hypothesized by Reta et al (24) .…”
Section: Discussionsupporting
confidence: 93%
“…These results concur with Reta et al (24) , who observed that the organs of the maize plants sown in spring developed better than the maize plants sown in summer. These results corroborate the observed variation among hybrids in relation to the total biomass production, and are consistent with others (12,38) who reported that the total yield of maize depends on the proper development of each of the plant components.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The high genetic diversity within the Argentine public maize inbred lines can also be observed at the phenotypic level. This collection currently harbours 17 inbreds that are parents of several recombinant inbred line (RIL) populations that are used to conduct conventional QTL studies for different agronomic traits (Sampietro et al ., 2009; Campos-Bermudez et al ., 2013; D'Andrea et al ., 2016) as part of the maize breeding program at INTA Pergamino (Argentina). In addition, these lines also show a high variation in colour and grain texture, yield, maturity and common rust resistance.…”
Section: Methodsmentioning
confidence: 99%
“…The assimilation of carbohydrates for grain-filled cereals are generally derived from two resources: (i) the current assimilates transferred directly to the grain and (ii) the assimilates redistributed from reserve pools in vegetative tissues either preanthesis or postanthesis ( Gan and Amasino, 1997 ; Gebbing and Schnyder, 1999 ). However, under conditions associated with low nitrogen or high density, grain filling is limited by matter accumulation and increased transport ( D’Andrea et al, 2016 ). As a result, the final grain weight decreases dramatically due to growth restrictions during the active grain-filling stage, and the accumulation of dry matter and the matter translocation rate have a decisive effect on grain filling ( Ntanos and Koutroubas, 2002 ).…”
Section: Introductionmentioning
confidence: 99%